Penggunaan Media Audiovisual Dengan Power Point di Tengah Pandemi dalam Pembelajaran Pendidikan Kewarganegaraan di Madrasah Ibtidaiyah - Dea Lita Salsabila; Heri Hidayat; Heny Mulyani; Dini Arlina; Delfianti Azzahra (IAI Al Khoziny Buduran Sidoarjo, 2020)
The use of audiovisual media is a strategy in student learning to determine the effect and development of teacher performance on students. During the Covid-19 pandemic, Civics learning, especially in Islamic Elementary School and Elementary School, contained audiovisual learning using Power point as a tool for presenting material that was well known among users of personal computers and laptops. In this study using several research methods in the form of secondary data with observations and experiences in accordance with the theme of learning through the media as well as utilizing library resources. Through the Audiovisual facility with Power Point, it shows the results of research in the form of the development of the reasoning power of students who are capable of actually being and increasing the learning process for students to a more professional level in the use of learning technology.